Complex fermion mass poles in the linear sigma model at finite temperature - Silva, Alisson Matheus Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
We investigate the appearance of unphysical complex-mass poles in the fermion propagator in the linear sigma model (LSM) at finite temperature. The LSM is an effective field theory for spontaneous chiral symmetry breaking (SCSB) in quantum chromodynamics (QCD). The effective degrees of freedom are described by scalar and pseudoscalar meson fields and spin-1/2 fermion fields. When the fermions are nucleons, the LSM model realizes SCSB in the confined phase of QCD, and when the fermions are quarks, it realizes SCSB in the QCD deconfined phase. The presence of complex poles in the propagators leads to unphysical results in observables such as in the thermodynamic equation of state and transport coefficients. Specifically, we quantify at the one-loop level the thermal contributions to the fermion self-energy spectral function and on the complex poles. We found that although temperature changes the spectral properties of the propagators, it does not eliminate the poles, but close to the chiral restoration temperature, there are significant qualitative changes in those quantities. We conclude with considerations about the implications of our results for the interpretation of the appearance of complex-mass poles in QCD propagators as signaling quark-gluon confinement.

Investigamos o surgimento de polos de massa complexa não físicos no propagador de férmions no modelo sigma linear (LSM) a temperatura finita. O LSM é uma teoria de campo efetiva para a quebra espontânea de simetria quiral (SCSB) na cromodinâmica quântica (QCD). Os graus de liberdade efetivos são descritos por campos de mésons escalares e pseudoscalars e campos de férmions de spin-1/2. Quando os férmions são núcleons, o modelo LSM realiza a SCSB na fase confinada da QCD, e quando os férmions são quarks, ele realiza a SCSB na fase desconfinada da QCD. A presença de polos complexos nos propagadores leva a resultados não físicos em observáveis, como na equação de estado termodinâmica e nos coeficientes de transporte. Especificamente, quantificamos no nível de um laço as contribuições térmicas à função espectral da autoenergia dos férmions e aos polos complexos. Descobrimos que, embora a temperatura altere as propriedades espectrais dos propagadores, ela não elimina os polos, mas, próximo à temperatura de restauração quiral, há mudanças qualitativas significativas nessas quantidades. Concluímos com considerações sobre as implicações dos nossos resultados para a interpretação do surgimento de polos de massa complexa nos propagadores da QCD como um sinal de confinamento quark-glúon.
Pólos de massa complexos de férmions no modelo sigma linear em temperatura finita
Keywords: Física nuclear; Cromodinâmica quântica